PENGARUH BRAND IMAGE DAN BRAND TRUST TERHADAP KEPUTUSAN PEMBELIAN SMART PHONE SAMSUNG (STUDI KASUS PERUMAHAN GRIYA 8 PERMAI BUMIAYU KOTA MALANG) - Ria Tasiana; Farah Adiba (STIA MALANG, 2022)
Having a strong brand image is a must for every company. Because the brand image is a very valuable company asset. It takes hard work and a long time to build a reputation and brand image. Consumers tend to trust products with preferred or well-known brands. This reason underlies the company to strengthen its brand position in order to create a positive brand image for consumers. Through brand image, consumers are able to recognize a product, evaluate its quality, reduce purchase risk, and gain experience and satisfaction from certain product differentiation. This study aims to analyze the effect of brand image and brand trust simultaneously on purchasing decisions for Samsung smartphones, analyze the effect of brand image and brand trust partially on purchasing decisions for Samsung smartphones. This study uses quantitative research methods. The type of approach that the researcher uses is a quantitative descriptive analysis approach with explanatory research. Data collection techniques using interviews and questionnaires. The data obtained in the form of data from primary data and secondary data. The population in this study were 369 people with a total sample of 79 respondents. Determination of the sample using purposive sampling technique. After the data was obtained, the data were analyzed quantitatively using multiple linear regression analysis, F test and t test. The results show that brand image and brand trust have a simultaneous effect on purchasing decisions, as evidenced by the F value of 28,042 with a significance level of 0.000. Brand image has a partial effect on purchasing decisions, as evidenced by the tcount value of 2,761 with a significance level of t of 0.007 < 0.05. Brand trust has a partial effect on purchasing decisions, as evidenced by the tcount value of 3.646 with a significance level of t of 0.000 <0.05.